A new monoclonal antibody (3A5) that recognises a fixative resistant epitope on tissue macrophages and monocytes. Issue 3 (March 1994) - Jaspars, E H; Bloemena, E; Bonnet, P; Scheper, R J; Kaiserling, E; Meijer, C J
Abstract : AIMS–To develop a monoclonal antibody specific for human macrophages in routinely processed material. METHODS–The monoclonal antibody was derived from a mouse popliteal lymph node after subcutaneous immunisation in the footpad with fragments of human spleen depleted of lymphocytes and erythrocytes. RESULTS–3A5 is a monoclonal antibody reactive with macrophages, monocytes, and histiocytes in routinely processed (formalin fixed, paraffin wax embedded) human tissue specimens. Unlike the well known panmacrophage marker KP1 (CD68), neither dendritic cells (interdigitating cells, Langerhans' cells, and microglia) nor myeloid, lymphoid, or epithelial cells stained with 3A5. CONCLUSION–As the staining pattern of 3A5 is restricted, compared with other macrophage markers and the recognised epitope survives common fixation and embedding procedures, 3A5 is a valuable marker for histiocytes and macrophages in routine diagnostic applications.